Baseline knee adduction moment interacts with body mass index to predict loss of medial tibial cartilage volume over 2.5 years in knee Osteoarthritis. Issue 11 (7th April 2017) - Brisson, Nicholas M.; Wiebenga, Emily G.; Stratford, Paul W.; Beattie, Karen A.; Totterman, Saara; Tamez‐Peña, José G.; Callaghan, Jack P.; Adachi, Jonathan D.; Maly, Monica R.
ABSTRACT: This study aimed to determine the extent to which changes over 2.5 years in medial knee cartilage thickness and volume were predicted by: (1) Peak values of the knee adduction (KAM) and flexion moments; and (2) KAM impulse and loading frequency, representing cumulative load, after controlling for age, sex and body mass index (BMI). Adults with clinical knee osteoarthritis participated. At baseline and approximately 2.5 years follow‐up, cartilage thickness and volume of the medial tibia and femur were segmented from magnetic resonance imaging scans. Gait kinematics and kinetics, and daily knee loading frequency were also collected at baseline. Multiple linear regressions predicted changes in cartilage morphology from baseline gait mechanics. Data were collected from 52 participants (41 women) [age 61.0 (6.9) y; BMI 28.5 (5.7) kg/m 2 ] over 2.56 (0.51) years. There were significant KAM peak‐by‐BMI ( p = 0.023) and KAM impulse‐by‐BMI ( p = 0.034) interactions, which revealed that larger joint loads in those with higher BMIs were associated with greater loss of medial tibial cartilage volume. In conclusion, with adjustments for age, sex, and cartilage measurement at baseline, large magnitude KAM peak and KAM impulse each interacted with BMI to predict loss of cartilage volume of the medial tibia over 2.5 years among individuals with knee osteoarthritis. These data suggest that, in clinical knee osteoarthritis, exposure to large KAMs may be detrimental to cartilage in those with larger BMIs. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:2476–2483, 2017.